Indicator of housing affordability in Malaysia - Md. Sani @ Abd. Rahim, Norazmawati; Che Munaaim, Muhammad Arkam (2008)
There are many indicator of housing affordability in Malaysia such as household income, household expenditure, house prices and others. If the income is adequate to pay for a house and other household expenditure, then the individual concerned can be described as having home affordability. The objective of this paper is to discuss the indicator of housing affordability in Malaysia and variables that affect housing affordability amongst the lowincome group in Malaysia. From the experience of developed countries, the indicators of housing affordability in Malaysia that affecting housing affordability are mainly house price and housing finance. The finding of this paper conducted on low-cost housing at Kuala Lumpur is there are two main indicator affecting housing affordability i.e. household income and household expenditure. In conclusion, the understanding of indicator of housing affordability in Malaysia are important as input to improve our housing policy.